Automatic rain water saver / Mohamad Ikhsan Abdullah Ibrahim & Amirul Faiq Mohd Hashim - Ibrahim, Mohamad Ikhsan; Mohd Hashim, Amirul Faiq (2015)
Automatic Rain Water -Saver is ·an inexpensive technology, can -be -implemented for several application such as for saving water in the container during rain and all many more home appliance. Automatic rain water saver technology nowadays which is a matured technology that has been widely deployed by various organization as part of their automation system for example -rain sensor and water sensor that programing to the arduino include with servo motor. The main objective of this project is to design and implement a automatic rain water saver that appliance can be controlled automatically by rain sensor and water sensor. In this project, we use servomotor to open the opener of the container. This project consists of two main parts which include the hardware and .the software. The hardware consists of the ATmega328 microcontroller (arduino UNO), water sensor, rain sensor, LCD displays 16X2, servo motor and also include with 3.3V-5V .converter. The serial communication will communicate to the host computer where it was interfaced with the arduino main board. The advantage of using this technology is it can save rainwater. We can use the water when our house cannot get the water supply. So this technology is inexpensive and very important to our daily life.